Pengaruh Kompensasi Non Finansial terhadap Kepuasan Kerja dan Dampaknya terhadap Kinerja Karyawan Universitas Baturaja - Asmaul Husnah; Yunita Sari; Mardiah Kenamon (Studi Ilmu Manajemen dan Organisasi, 2024)
Purpose: The writing of research aimed to give analysys regarding the impact of non-financial compensation on job satisfaction and its effect on the performance of Baturaja University.Methodology: This study used a quantitative method. Data was collected by creating a research instrument that was distributed to 53 employees of Baturaja University as the research sample and analyzed using path analysisResults: The results of the study show that there is a significant effect of non-financial compensation on employee performance through the mediation of the job satisfaction variableConclusions: Non-financial compensation significantly affects employee job satisfaction and performance at Universitas Baturaja, with job satisfaction acting as a mediator. The management should improve non-financial compensation to enhance employee performance.Limitations: This study has limitations in terms of the sample, which is restricted to employees with a tenure of 3 years after being appointed as permanent employees, totaling 53 people. It is hoped that the sample size and other independent factors can be expanded for future research. Variables such as the work environment, leadership, career development, and other related topics may also influence the improvement of employee performance.Contribution: As additional information to expand knowledge, it can also be used as a reference for researchers who will conduct similar studies in the future. Furthermore, it can provide input or contribute ideas to the University in improving employee performance through satisfaction indicators, so that employee performance becomes better and aligns with the University's Vision and Mission.